IDENTIFIKASI ATRIBUT PELAYANAN DAN TINGKAT KEPUASAN KONSUMEN RUMAH MAKAN BAKSO DI LINGKUNGAN UNIVERSITAS LAMPUNG - Magdalena Meiliani; Yaktiworo Indriani; Zainal Abidin (Lampung University, 2019)
The aims of this research are to analyze customer’s characteristics, attributes of meatball and services, customer satisfaction; in addition to aplication of attributes and services of meatball restaurant. The data was collected in Januari-Maret 2018. The research location was determined purposively at Restaurant A, B and C, surrounding The university of lampung (Unila). The technique used for sampling was accidental sampling, involving 99 students as respondents. Data was analyzed descriptively by Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The result showed that the consumers were mostly women students at Unila, 21-23 years old of age, having pocket money of Rp500,000 to 1,000,000 per month. The identified meatball attributes were taste, aroma, size of bowl, display of meatball, price, product guarantee, service alertness, service justice, availability of parking area, accessibility of location, cleanliness and employee hospitality. Consumer satisfaction value at Restaurant A, B, C was 70.20%; 71.80% and 67.80% respectively; it meant that customers were satisfied. The attributes needed to be improved at Restaurant A were product guarantee and employee hospitality, while at Restaurant B were price, service justice, service alertness, and employee patience.Key words: attributes, CSI, IPA, meatball, satisfaction